2014
DOI: 10.2319/062813-480.1
|View full text |Cite
|
Sign up to set email alerts
|

Malocclusion and orthodontic treatment need evaluated among subjects with Down syndrome using the Dental Aesthetic Index (DAI)

Abstract: Most of the subjects with DS (94; 83.2%) had severe and very severe malocclusion, which indicated a desirable and mandatory need for orthodontic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Indeed, the primary skeletal abnormality affecting the orofacial structures in DS is the underdevelopment or hypoplasia of the midface region . A high prevalence of anterior open bite among DS individuals has also been reported in the literature . The insufficient maxilla development associated with orofacial muscle hypotonia, a high prevalence of deleterious habits, such as thumb sucking and mouth breathing as well as the abnormal function and the position of the tongue, seems to be responsible for the high prevalence of anterior open bite .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, the primary skeletal abnormality affecting the orofacial structures in DS is the underdevelopment or hypoplasia of the midface region . A high prevalence of anterior open bite among DS individuals has also been reported in the literature . The insufficient maxilla development associated with orofacial muscle hypotonia, a high prevalence of deleterious habits, such as thumb sucking and mouth breathing as well as the abnormal function and the position of the tongue, seems to be responsible for the high prevalence of anterior open bite .…”
Section: Discussionmentioning
confidence: 96%
“…The most frequent craniofacial characteristics observed among DS children/adolescents are reduction in cranial size and flattened cranial base, midface hypoplasia with deviations in shape, size, and/or position of the maxilla and mandible. Nasal bone depression and flat facial profile, high palate, hypotonicity of the perioral muscles, a relatively large, protruding and hypotonic tongue, narrowed oropharynx, inclined palpebral fissures, strabismus, and dental anomalies of number and shape are also observed …”
Section: Introductionmentioning
confidence: 99%
“…In this study crowding, lateral cross‐bite, agenesis of one or more permanent teeth, and inverted anterior teeth were the most prevalent traits. These findings are consistent with the study by Abdul Rahim et al ., in which children with DS were found to have significant need for orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The desire for improvement in dental appearance and psychosocial well‐being is therefore a common motivation for seeking orthodontic treatment . A high prevalence of malocclusion was reported in Malaysian children and adults with DS in a prior study using the Dental Aesthetic Index (DAI) . However, the age‐specific prevalence of malocclusion in school‐age children with DS has not been well studied and there are no interdisciplinary national guidelines or consensus for the treatment and follow up of hypodontia and malocclusion in children with DS in Norway.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies have reported up to 95% or higher prevalence of malocclusion among children with disabilities [7,8]. The reported prevalence of malocclusion in the general population ranges from 22 to 76 percent [9,10].…”
Section: Introductionmentioning
confidence: 99%